Association between vaccination status, symptom identification and healthcare use: Implications for test negative design observational studies. Issue 13 (18th March 2022) - El-Heneidy, Asmaa; Grimwood, Keith; Lambert, Stephen B.; Sarna, Mohinder; Ware, Robert S.
Abstract: Aim: To test the internal validity of the test-negative design (TND) by investigating associations between maternal influenza vaccination, and new virus detection episodes (VDEs), acute respiratory illness, and healthcare visits in their children. Methods: Eighty-five children from a birth cohort provided daily symptoms, weekly nasal swabs, and healthcare use data until age 2-years. Effect estimates are summarised as incidence rate ratios (IRR). Results: There was no association between maternal vaccination and VDEs in children (IRR = 1.1; 95 %CI = 0.9–1.2). Influenza-vaccinated mothers were more likely than unvaccinated mothers to both report, and seek healthcare for, acute lower respiratory illness in their children, IRR = 2.4; 95 %CI = 1.2–4.8 and IRR = 2.2; 95 %CI = 1.1–4.3, respectively. Conclusion: A key assumption of the TND, that healthcare seeking behaviour for conditions of the same severity is not associated with vaccine receipt, did not hold. Further studies of the performance of the TND in different populations are required to confirm its validity.